Goldberg Coupling of Thiazole Substituted Aryl Bromide Demands Stoichiometric Copper Compared to Oxazole. Issue 5 (2nd February 2022) - Ahmad, Haseen; Ahmed, Waqar; Hassan, Abbas
Abstract: The C−N functionalization of thiazole appendant aryl halides using copper mediated transformation has the potential as a strategy for late‐stage Goldberg coupling of carboxamide and heteroaryl halide. The C−N coupling of thiazole scaffold in the presence of copper is highly challenging. The current work presents the C−N coupling of various amides with thiazole derivatives that afforded variety of amide products. The 4‐(4‐bromo‐phenyl)‐2‐methylthiazole, 4‐(4‐bromophenyl)‐2‐pyridiythiazole and 4‐(3‐bromophenyl)‐2‐methylthiazole reacted with aliphatic, aromatic and cyclic amides smoothly in the presence of stoichiometric amount of copper iodide and N, N' ‐DMEDA resulting in C−N bond formation in high yields. The reaction optimization attest to the requirement of stoichiometric amount of copper for the thiazolyl aryl bromide. While the corresponding oxazole can easily undergo the amide coupling employing only catalytic amount of copper. Abstract : Thiazole structural unit is found in many synthetic drugs. The basic heteroatom may strongly bound to transition metal to deactivate its catalytic ability. We have showed that thiazole bearing aryl bromide when subjected to Goldberg reaction, proceeds with stoichiometric amount of copper unlike the corresponding oxazole derivatives.